Lesions with unclear malignant potential (B3) after minimally invasive breast biopsy: evaluation of vacuum biopsies performed in Switzerland and recommended further management - Saladin, Camilla (Acta Radiol, 2015)
BACKGROUND: Histopathological B3 lesions after minimal invasive breast biopsy (VABB) are a particular challenge for the clinician, as there are currently no binding recommendations regarding the subsequent procedure. PURPOSE: To analyze all B3 lesions, diagnosed at VABB and captured in the national central Swiss MIBB database and to provide a data basis for further management in this subgroup of patients. MATERIAL AND METHODS: All 9,153 stereotactically, sonographically, or magnetic resonance imaging (MRI)-guided vacuum-assisted breast biopsies, performed in Switzerland between 2009 and 2011, captured in a central database, were evaluated. The rate of B3 lesions and the definitive pathological findings in patients who underwent surgical resection were analyzed. RESULTS: The B3 rate was 17.0% (1532 of 9000 biopsies with B classification). Among the 521 lesions with a definitive postoperative diagnosis, the malignancy rate (invasive carcinoma or DCIS) was 21.5%. In patients with atypical ductal hyperplasia, papillary lesions, flat epithelial atypia, lobular neoplasia, and radial scar diagnosed by VABB, the malignancy rates were 25.9%, 3.1%, 18.3%, 26.4%, and 11.1%, respectively. CONCLUSION: B3 lesions, comprising 17%, of all analyzed biopsies, were common and the proportion of malignancies in those lesions undergoing subsequent surgical excision was high (21.5%).